Protect, Track, Emancipate: The Role of Political Masculinities in India's Fight against Sex Selection. (August 2019) - Rahm, Laura
One of the side effects of India's rapid socioeconomic transition has been a growing demographic masculinization with millions of "missing" women. Modern technologies have enabled couples to determine and select the fetal sex. Since the 1990s, political efforts to control sex selection have met with little success. This article assesses policy effectiveness and the role of political masculinities in India's fight against sex selection. This qualitative analysis draws from policy files and forty-seven in-depth semistructured expert interviews conducted in Delhi, Punjab, and Haryana in 2014–2015. Interview participants included national policy makers, state and district implementers, and representatives from nongovernmental and international organizations. This article finds that state action against sex selection frequently follows the logic of "protecting, " "tracking, " and "emancipating" females—analogue to roles of a family patriarch toward his kin and thus reproducing gender biases and undermining policy efforts against sex selection.